Analisis Implementasi Keterampilan Komunikasi Staf UPT Humas UNNES di Era Digitalisasi - Indah Ayu Cahyani; Oktarina, Nina (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The 21st century as the century of globalization emphasizes the massive use of information technology, which has an impact on the need for competent human resources, including communication skills. The duties of a public relations officer related to information dissemination certainly have an impact on the need for digital and multiplatform communication skills. Therefore, the purpose of this study is to analyze the implementation of communication skills of UNNES Public Relations staff in the era of digitalization using the digital communication skills indicators of DigComp 2.0 by Ferrari (2013). This study uses a qualitative descriptive analysis research method. Data were collected through interviews, observations, and documentation. The results showed that the implementation of communication skills in the three divisions of the UNNES Public Relations Technical Implementation Unit (UPT) had a high level of adaptability in the digital work ecosystem, applied dynamic, audience-oriented communication strategies, and utilized cloud-based work systems for efficiency. Ethically, staff demonstrated good digital maturity with quality control through tiered verification, although there were no specific written guidelines. These findings confirm that digital communication competence is not limited to technical skills alone, but also includes data analysis skills and is supported by written company guidelines as an official reference.